2021
DOI: 10.1007/s00392-021-01971-3
|View full text |Cite
|
Sign up to set email alerts
|

Time to abandon ampicillin plus gentamicin in favour of ampicillin plus ceftriaxone in Enterococcus faecalis infective endocarditis? A meta-analysis of comparative trials

Abstract: Background Current guidelines recommend either ampicillin plus ceftriaxone (AC) or amoxicillin/ampicillin plus gentamicin (AG) with an equivalent class IB recommendation in Enterococcus faecalis endocarditis. However, previous observational studies suggest that AC might be favourable in terms of adverse events. Objectives To investigate whether AC is non-inferior to AG, and if it is associated with less adverse events. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Accordingly, therapeutic drug monitoring is essential in this population, especially when using narrow therapeutic index antibiotics [ 100 , 101 , 102 ]. A reduction in aminoglycoside use, recommended in the latest guidelines (no longer recommended in Staphylococcus aureus native-valve IE and shortened to 2 weeks in Enterococcus faecalis and streptococci with penicillin MIC > 0.125 μg/mL) [ 9 ], as well as aminoglycoside replacement by ceftriaxone in E. faecalis treatment [ 103 , 104 , 105 , 106 ], should be preferential in older people [ 107 , 108 ]. Despite recent efforts to improve vancomycin drug monitoring [ 100 , 101 , 109 , 110 ], daptomycin has shown a lower risk of clinical failure and treatment-limiting AEs than vancomycin [ 111 , 112 , 113 , 114 ] and should be preferentially used when available.…”
Section: Antibiotic Treatment: the Shorter The Better Diminishing Int...mentioning
confidence: 99%
“…Accordingly, therapeutic drug monitoring is essential in this population, especially when using narrow therapeutic index antibiotics [ 100 , 101 , 102 ]. A reduction in aminoglycoside use, recommended in the latest guidelines (no longer recommended in Staphylococcus aureus native-valve IE and shortened to 2 weeks in Enterococcus faecalis and streptococci with penicillin MIC > 0.125 μg/mL) [ 9 ], as well as aminoglycoside replacement by ceftriaxone in E. faecalis treatment [ 103 , 104 , 105 , 106 ], should be preferential in older people [ 107 , 108 ]. Despite recent efforts to improve vancomycin drug monitoring [ 100 , 101 , 109 , 110 ], daptomycin has shown a lower risk of clinical failure and treatment-limiting AEs than vancomycin [ 111 , 112 , 113 , 114 ] and should be preferentially used when available.…”
Section: Antibiotic Treatment: the Shorter The Better Diminishing Int...mentioning
confidence: 99%
“…Most WikiGuidelines authors suggest against routine use of adjunctive aminoglycosides because of a lack of evidence of benefit with a demonstrable risk of harm (discussed in eAppendix 3 in Supplement 1). Options for definitive intravenous therapy by organism are presented in Table 2, with nuanced discussions in eAppendix 3 in Supplement 1 …”
Section: Resultsmentioning
confidence: 99%
“…Options for definitive intravenous therapy by organism are presented in Table 2, with nuanced discussions in eAppendix 3 in Supplement 1. [54][55][56][57][58][59][60] Question 3: Can Oral Antimicrobial Therapy Be Used to Treat IE? (Clear Recommendation)…”
Section: Question 2: Which Antibiotics Are Appropriate For Antibiotic...mentioning
confidence: 99%
See 1 more Smart Citation
“…This dual therapy has the disadvantage of a high risk of acute kidney injury (25% of patients) and loses its synergistic effect against isolates with high-level aminoglycoside resistance (HLAR) [ 10 , 11 ]. The combination of ampicillin and ceftriaxone has shown synergistic activity in vitro against E. faecalis, and retrospective studies have shown that this combination had a similar clinical cure rate for EFIE as the A-G combination, with a better safety profile [ 10 , 12 , 13 ].…”
mentioning
confidence: 99%